Little Fire Ant, Wasmannia auropunctata (Roger) (Insecta: Hymenoptera: Formicidae) - Shawn Brooks; J. C. Nickerson (EDIS)
Prior to the advent of chlorinated hydrocarbons, organophosphates, and carbamates the little fire ant, Wasmannia auropunctata (Roger), was a problem in Florida. The use of persistent pesticide chemicals reduced the populations of the ants until they were no longer a menace. With the reduction in the use of these persistent pesticide chemicals populations of little fire ants have been allowed to increase, and in some areas, to develop into a serious problem.  This document is EENY-139 (originally published as DPI Entomology Circular No. 248), one of a series of Featured Creatures from the Entomology and Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: June 2000.